The nonlinear Dirac equation in Bose-Einstein condensates: superfluid fluctuations and emergent theories from relativistic linear stability equations - Haddad, Laith H.; Carr, Lincoln D. (New journal of physics, 2015)
We present the theoretical and mathematical foundations of stability analysis for a Bose–Einstein condensate (BEC) at Dirac points of a honeycomb optical lattice. The combination of s-wave scattering for bosons and lattice interaction places constraints on the mean-field description, and hence on vortex configurations in the Bloch-envelope function near the Dirac point. A full derivation of the relativistic linear stability equations (RLSE) is presented by two independent methods to ensure veracity of our results. Solutions of the RLSE are used to compute fluctuations and lifetimes of vortex solutions of the nonlinear Dirac equation, which include Anderson–Toulouseskyrmions with lifetime »4 s. Beyond vortex stabilities the RLSE provide insight into the character of collective superfluid excitations, which we find to encode several established theories of physics. In particular, the RLSE reduce to the Andreev equations, in the nonrelativistic and semiclassical limits, the Majorana equation, inside vortex cores, and the Dirac–Bogoliubov–de Gennes equations, when nearestneighbor interactions are included. Furthermore, by tuning a mass gap, relative strengths of various spinor couplings, for the small and large quasiparticle momentum regimes, we obtain weak-strong Bardeen–Cooper–Schrieffer superconductivity, as well as fundamental wave equations such as Schrödinger, Dirac, Klein–Gordon, and Bogoliubov–de Gennes equations. Our results apply equally to astrongly spin–orbit coupled BEC in which the Laplacian contribution can be neglected.
Gesehen am 03.03.2021